High-dose vitamin D versus placebo to prevent complications in COVID-19 patients: Multicentre randomized controlled clinical trial. - Javier Mariani; Laura Antonietti; Carlos Tajer; León Ferder; Felipe Inserra; Milagro Sanchez Cunto; Diego Brosio; Fernando Ross; Marcelo Zylberman; Daniel Emilio López; Cecilia Luna Hisano; Sebastián Maristany Batisda; et al. (PLoS ONE, 2022)
Background The role of oral vitamin D3 supplementation for hospitalized patients with COVID-19 remains to be determined. The study was aimed to evaluate whether vitamin D3 supplementation could prevent respiratory worsening among hospitalized patients with COVID-19. Methods and findings We designed a multicentre, randomized, double-blind, sequential, placebo-controlled clinical trial. The study was conducted in 17 second and third level hospitals, located in four provinces of Argentina, from 14 August 2020 to 22 June 2021. We enrolled 218 adult patients, hospitalized in general wards with SARS-CoV-2 confirmed infection, mild-to-moderate COVID-19 and risk factors for disease progression. Participants were randomized to a single oral dose of 500 000 IU of vitamin D3 or matching placebo. Randomization ratio was 1:1, with permuted blocks and stratified for study site, diabetes and age (≤60 vs >60 years). The primary outcome was the change in the respiratory Sepsis related Organ Failure Assessment score between baseline and the highest value recorded up to day 7. Secondary outcomes included the length of hospital stay; intensive care unit admission; and in-hospital mortality. Overall, 115 participants were assigned to vitamin D3 and 105 to placebo (mean [SD] age, 59.1 [10.7] years; 103 [47.2%] women). There were no significant differences in the primary outcome between groups (median [IQR] 0.0 [0.0-1.0] vs 0.0 [0.0-1.0], for vitamin D3 and placebo, respectively; p = 0.925). Median [IQR] length of hospital stay was not significantly different between vitamin D3 group (6.0 [4.0-9.0] days) and placebo group (6.0 [4.0-10.0] days; p = 0.632). There were no significant differences for intensive care unit admissions (7.8% vs 10.7%; RR 0.73; 95% CI 0.32 to 1.70; p = 0.622), or in-hospital mortality (4.3% vs 1.9%; RR 2.24; 95% CI 0.44 to 11.29; p = 0.451). There were no significant differences in serious adverse events (vitamin D3 = 14.8%, placebo = 11.7%). Conclusions Among hospitalized patients with mild-to-moderate COVID-19 and risk factors, a single high oral dose of vitamin D3 as compared with placebo, did not prevent the respiratory worsening. Trial registration ClincicalTrials.gov Identifier: NCT04411446.